British Rule and Muslim Education in Ago-Iwoye: The Historical Metaphors in Twentieth Century Pedagogy - Hashimi, A. O. (NIU Journal of Humanities, 2020)
Colonialism has attracted a lot of academic interest all over the World, this accounts for many studies carried out in various disciplines on colonial temper in African history. The themes of the studies focus more on the socio-political, religious-economic, educational and cultural implication of post colonialism and effects on the people. British rulers occupied Ijebu towns in Yorubaland in Nigeria, through the superiority and supremacy of military prowess at Magbon war of 1892, where thousands of Ijebu fell. This exterminative war against the Ijebu , installed British rulers over the people. This paper examines the British rule and Muslim education in Ago-Iwoye. The study employs analytical research method .Colonial education was largely dominated by the missionaries and when the Wesley primary school was established in the town in 1893, it was exclusive preserve of mission boards and consequently, conversion of Muslim children to Christianity took place. In responses to the colonial exploits, Muslims employed strategies which included avoidance, withdrawal submission, confrontation and alliance. The findings of this study x-ray the effects of the British rule disillusionments on the growth of Islam and education of Muslim children. The colonial character and actions portrayed a mighty and power at war with Islam. The study establishes a constitutive relationship between the British rulers and Christian evangelists in the town. Keywords: Ago-Iwoye, British rule, Muslim education, Colonialism, Evangelism